"Firearm access in dementia: legal and logistic challenges for caregivers". (3rd October 2021) - Polzer, Evan; Nearing, Kathryn; Knoepke, Christopher E.; Matlock, Daniel D.; McCourt, Alexander; Betz, Marian E.
Abstract: The prevalence of Alzheimer's disease and related dementias (ADRD) is increasing. In the United States, older adults are among those most likely to have firearms in the home. Addressing firearm access among persons with ADRD can be confusing and stressful for family caregivers, healthcare providers, firearm industry representatives and law enforcement. This study sought to examine key stakeholder perspectives concerning legal and logistic considerations for temporary firearm transfers when a person with ADRD owned firearms. A secondary analysis of 24 qualitative interviews conducted to inform the development of a firearm safety tool for ADRD caregivers revealed four types of barriers. These barriers were each associated with logistical challenges and legal ambiguities that hampered ADRD-related firearm transfers: (1) legal questions on firearm ownership and permitted transferees; (2) transfer logistics and duration; (3) issues of engaging law enforcement or retailers for transfers; and, (4) lack of information resources and guidance. Siloes between stakeholder groups persist and limit information sharing. Broad initiatives engaging caregivers, older adults, clinicians, aging service providers, law enforcement, and firearm outlets could inform the development of policies, programs, and practices to enhance the safety and well-being of people with ADRD and their caregivers.